(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This study examines vulnerability in acting using bioethics, social sciences and psychology revealing it as a crucial and significant aspect for further development. To observe, develop and apply vulnerability to acting, Coletiva Teatro divides the creative process in phases as a methodical parameter. From Stanislavski’s, Fabião’s, and Féral’s perspectives on acting, vulnerability reveals itself as pertinent for projects involving acting, performance and performative theatre. The observation of vulnerability and its respective vulnerating agents allows the recognition of its operating modes and the search for creative solutions that enable a healthy and productive relationship with it as a potent artistic tool.